Value-Based Management and Character Development in Islamic Boarding Schools: A Systematic Review - Sutikno Sutikno (Universitas Nurul Jadid, 2026)
This study aims to formulate a value-based Islamic educational management model for strengthening santri character development in pesantren dormitories. Pesantren have long functioned as centers of religious learning and moral formation in Indonesia; however, character education is often practiced through inherited traditions, while systematic management mechanisms remain limited. This study employed a qualitative integrative literature review to synthesize empirical sources on pesantren education, Islamic education management, and character development. Following PRISMA procedures, 64 sources were identified, 35 were selected, and the data were analyzed using thematic content analysis in NVivo 12 Plus. The findings show that santri character development is rooted in ta’dib, tawhid, worship, akhlaq, and moral habituation. Character formation emerges as a holistic process involving cognitive, affective, moral, social, and spiritual dimensions. Dormitory life functions as a hidden curriculum through exemplary leadership, habituation, supervision, and communal discipline. Effective development requires structured planning, organizing, implementation, supervision, evaluation, and adaptive Islamic management. The implications indicate that pesantren leaders should institutionalize value-based character education programs that are systematic, measurable, sustainable, and responsive to contemporary educational challenges, while integrating Islamic moral values, dormitory-based habituation, and educational management functions into a coherent framework for stronger, accountable, and contextually relevant santri character formation in pesantren.